2019
DOI: 10.1002/aenm.201902773
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Visualization of Electrochemical Lithiation Processes in Monolayer MoS2 by Cryogenic Electron Microscopy

Abstract: While lithium ion batteries with electrodes based on intercalation compounds have dominated the portable energy storage market for decades, the energy density of these materials is fundamentally limited. Today, rapidly growing demand for this type of energy storage is driving research into materials that utilize alternative reaction mechanisms to enable higher energy densities. Transition metal compounds are one such class of materials, with storage enabled by “conversion” reactions, where the material is conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 45 publications
(45 reference statements)
1
28
0
Order By: Relevance
“…1). Bilayer MoS2 on the other hand undergoes an intercalation reaction before conversion to Mo and Li2S nanoparticles [9]. The cryo-STEM imaging stability demonstrated here, have allowed us to gain unique atomic-scale insights into the lithiation processes 2D layered materials down to the monolayer limit.…”
mentioning
confidence: 76%
“…1). Bilayer MoS2 on the other hand undergoes an intercalation reaction before conversion to Mo and Li2S nanoparticles [9]. The cryo-STEM imaging stability demonstrated here, have allowed us to gain unique atomic-scale insights into the lithiation processes 2D layered materials down to the monolayer limit.…”
mentioning
confidence: 76%
“…[138,180,359,360] There are also difficulties in evaluating and controlling the degree of intercalation since the incomplete intercalation has been shown to produce low yields of monolayer products, while the intermediate Li x TMDCs with corresponding metal nanoparticles and chalcogens are decomposed over the insertion. [252,343,361,362] Electrochemical Intercalation: The electrochemical technique is also employed as a quick and controllable tool for lithium intercalation [344,[363][364][365][366][367][368][369] and considered as an effective technique for exfoliating and/or intercalates layered material to single or multilayered 2D nanosheets, summary of electrochemical exfoliation of various bulk TMDCs summarized in Table 5. [63,[370][371][372] Electrochemical reactions that have occurred on electrode with layered structure will yields as intercalation and/or exfoliation of electrode.…”
Section: Intercalation Routesmentioning
confidence: 99%
“…Apart from designing different nanostructured MoS 2 ‐based materials for battery applications, the fundamental understanding of reaction mechanisms, structural properties, and phase transitions is vital to the development of improved electrode materials. A series of in situ techniques, including XRD, X‐ray absorption spectroscopy (XAS), Raman, and TEM, have been adopted to provide insights into the electrochemical mechanisms related to MoS 2 ‐based electrodes, see Table . Ex situ characterization methods require the cells to be disassembled and probed at different discharge–charge states searching for clues about electrochemical mechanisms of electrode materials.…”
Section: In Situ and Operando Studies Of Electrochemical Mechanism Ofmentioning
confidence: 99%
“…Upon further lithiation, Li x MoS 2 decomposes to form Li 2 S and Mo. Figure a shows the in situ XRD pattern obtained for bulk MoS 2 during the first discharge and charge cycle at a current density of 100 mA g −1 . It is found that the MoS 2 (003) peak downshifted during discharge, indicating the expansion in the c ‐axis after Li + intercalation with the formation of Li x MoS 2 (0< x <1).…”
Section: In Situ and Operando Studies Of Electrochemical Mechanism Ofmentioning
confidence: 99%